Interação entre Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae) e Heterorhabditis bacteriophora Poinar, 1976 (Rhabditida: Heterorhabditidae) no parasitismo de Diatraea saccharalis (Fabricius, 1974) (Lepidoptera Crambidae) - Silva, Telliane Santos Salgueiro (2020)
Entomopathogenic nematodes (EPNs) are considered beneficial microorganism, however, they can affect beneficial insects, such as parasitoids. The objective of this work was to evaluate the interaction between the larval endoparasitoid Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae) and the nematode Heterorhabditis bacteriophora Poinar, 1976 (Rhabditida: Heterorhabditidae), in the control of the sugarcane borer Diatraea saccharalis (Fabricius, 1974) (Lepidoptera: Crambidae), contributing to the decision-making process for the use of biological control in integrated pest management (IPM) by sugarcane producers. Diatraea saccharalis caterpillars were offered to C. flavipes females for parasitism. Subsequently, every 3 days, EPNs were inoculated. After mortality (which occurred after the second day of inoculation), it was waited 4 days to dissect D. saccharalis. Results show that EPNs are capable of killing D. saccharalis caterpillars in 48 hours, also killing the pupa and adult phases of the same insect. The results also show that EPNs invade the body of C. flavipes still inside D. saccharalis, thus preventing the development of the endoparasitoid. It can be concluded that there is intraguild competition between the biological control agents, but they can be used in the IPM, respecting a period between their applications. After the release of the endoparasitoid C. flavipes, 9 to 12 days should be waited for application of EPNs, so its development will not be hindered, taking advantage of the efficiency of the two natural enemies in the field.